Inoculum-disease relationships in Sclerotinia rot of Indian mustard (Brassica juncea) - ASHA SHIVPURI, R.P. GHASOLIA1* and (Indian Phytopathology, 2009)
Pot trials were conducted to compare the ability of the inoculum for the development of Sclerotinia rot of Indian mustard, induced by Sclerotinia sclerotiorum (Lib.) de Bary, using T-59 (Varuna) as a test variety. Different ages (5, 10, 15, 20 and 30-days) each with three loads (10, 20 and 30 g), influence of age of the plants (0-80 days) and 5 inoculation techniques were compared. In general, the disease incidence increased with increase in the density of inoculum and decreased with increase in the age of inoculum. The 5-day-old inoculum with 20 g load was caused 88 per cent disease incidence followed by 10 and 15-day-old inoculums with the same inoculum density. With regard to influence of the age of host plants, it was found that younger plants i.e. up to age of 40-days were highly susceptible showing higher range of disease incidence (52.5-84%) as compared to older ones. Inoculation either by placing single mycelial disc (5 mm) at collar region of plants or by placing inoculum led sorghum grains (4 / plant) around stem base of 30-day-old plants were found appropriate and more disease reproducible (83.1-84.3%) technique compare to other techniques.